ANALISIS KUALITAS PELAYANAN FRONT OFFICE (STUDI KASUS DI DINAS PENDIDIKAN KOTA BATU) - Aninda Tri Safinatun Najah (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
This study aims to analyze the quality of front office services at the Department of Education in Batu City by evaluating five main dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research method employed is a qualitative approach with a case study. The findings indicate that, overall, the quality of front office services at the Department of Education in Batu City is satisfactory. The tangibles dimension, such as cleanliness and facility comfort, and the reliability dimension, including staff consistency in performing tasks according to procedure, were rated positively. Responsiveness is demonstrated by the promptness in handling requests, supported by a facial recognition-based attendance system that enhances work efficiency. The assurance dimension was also positively assessed, showing a sense of security and comfort for the public. However, the empathy aspect still has room for improvement, particularly in providing clearer communication and more detailed information. Overall, this study recommends enhancing efficiency and information clarity to better meet public needs.